THD Improvement for Variable Speed Drive Using Single Phase Multilevel Inverter - Alhalali, Safoan M. O. (2006)
Low harmonic waveform is a very important requirement of the high power applications. Nowadays many researchers are focusing on new voltage source. Such voltage sources are formed by Cascade H-bridge Multilevel Inverter with low Total Harmonic Distortion (THD). A multilevel inverter has wide applications especially for High-Power Electrical Vehicle motor drive because they convert small DC voltage to high AC voltage. This study investigates the performance and discusses the features of transformer and transformer-less multilevel inverters. In order to generate sinusoidal wave with minimum total harmonic distortion, one approach has been adapted to calculate the conducting angles. Simple external circuit was employed to equalize the magnetic flux via each transformer which makes it more efficient in order of the manufacturability. All H-bridge will have the same specifications which enhance the modularity of the system. THD values have been measured experimentally and from simulation results, the results show a good agreement with latest research. The experimental result has been compared with the simulation values, considerable difference have been notice because the effect of some factor such as the difference in components quality and the precise of the microcontroller. The PIC microcontroller was used to generate the gate signals and controlling the swapping circuit. The proposed circuits were simulated using Orcad/Pspice and experimental prototype was build as a drive for single phase induction motor based voltage 1 frequency method to show the validity of this system. Simulation of the diode clamped and transformer-less cascade multilevel inverter has been carried out to investigate their features.